2007
DOI: 10.1093/tropej/fmm069
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection and Gastroesophageal Reflux in Asthmatic Children

Abstract: The aim of this article is to investigate the prevalence of Helicobacter pylori (HP) infection, frequency of gastroesophageal reflux (GER), existence of atopy and levels of serum immunoglobulin E (IgE) in children with bronchial asthma. One hundred and thirty seven children who were diagnosed as bronchial asthma and/or wheezy child aged between 1 and 17 years were enrolled into the study. Peripheral venous blood samples were obtained to determine the total IgE and HP IgG antibody levels. GER was evaluated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…An additionally 99 stool samples were lost during transport to the final laboratory. Children reporting chronic cough/asthma were included as no studies have not shown significant elevated concentrations of faecal calprotectin in children with asthma [25]. …”
Section: Methodsmentioning
confidence: 99%
“…An additionally 99 stool samples were lost during transport to the final laboratory. Children reporting chronic cough/asthma were included as no studies have not shown significant elevated concentrations of faecal calprotectin in children with asthma [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Fourteen potential participants (3.1%) were excluded into the final analysis due to medical conditions (3), positive HIV test (5), failure to produce a stool sample in 3 days (5), incomplete data (1), figure 1. Children reporting chronic cough/asthma were included as other studies have not shown a significant correlation between Helicobacter pylori colonization and asthma [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Asthma is the leading cause of chronic childhood illness in the United States, affecting approximately 54 of 1,000 children. In the pediatric population, GERD is increasingly postulated as a potential causative agent for asthma [7,12,13]. Consistent with this idea, a recent study demonstrated that 87% of children with asthma experienced pathologic GERD, as monitored by 24-h esophageal pH monitoring [14].…”
mentioning
confidence: 94%